Analisis Model Fulmer Dan Grover Dalam Memprediksi Financial Distress Pada Industri Barang Konsumsi - Putri, Rianita; Werastuti, Desak Nyoman Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine whether Fulmer and Grover models can predict financial distress in the consumer goods industry and compared which prediction models has the highest level of accuracy. The type of research was quantitative research. The population of the study was the companies in the consumer goods industry. This research period was from 2015-2018 with 124 samples divided into two categories, as the financial distress category (1) as many as 21 samples and the non financial distress category as many as 103 samples. The sampling method used was purposive sampling. The sample would be analyzed through descriptive statistical, multicollinearity assumption test, logistic regression, and calculated the level of accuracy and errors. The result showed that (1) the Fulmer models can be used in predicted financial distress with 6 ratios has a significant effect and 3 ratios has no significant effect toward financial distress. (2) Grover models can be used in predicted financial distress with 3 ratio has a significant effect toward financial distress. (3) The model that has highest level of accuracy in predicted financial distress in the consumer goods industry was Fulmer at 84,68%, followed by Grover at 78,23%.